2016
DOI: 10.5535/arm.2016.40.2.318
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Activation of Serratus Anterior, Trapezius and Latissimus Dorsi With Slouched Posture

Abstract: ObjectiveTo compare quantitative muscle activation between erect and slouched sitting postures in the muscles around the scapula, and to investigate the correlation between the angle of thoracic kyphosis and the alteration of muscle activity depending on two different sitting postures.MethodsTen healthy males participated in the study. Unilateral surface electromyography (SEMG) was performed for serratus anterior, middle trapezius (MT), and lower trapezius (LT), which are scapular stabilizer muscles, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 25 publications
0
20
1
Order By: Relevance
“…[21][22][23] Electromyography is also very commonly used in postural assessment studies to ascertain the changes in muscular activities that occur as a result of postural changes. 24 Most previous studies mention the causes and consequences of FHP, rounded shoulders, and increased thoracic kyphosis. However, there is a dearth of studies focused on the association between forward head, rounded shoulders, and hyperkyphosis.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Electromyography is also very commonly used in postural assessment studies to ascertain the changes in muscular activities that occur as a result of postural changes. 24 Most previous studies mention the causes and consequences of FHP, rounded shoulders, and increased thoracic kyphosis. However, there is a dearth of studies focused on the association between forward head, rounded shoulders, and hyperkyphosis.…”
Section: Introductionmentioning
confidence: 99%
“…Pain could also be affected by musculoskeletal factors, such as a slouched sitting posture. In sedentary young adult males, it has been demonstrated that changing a specific position may influence pain level [31,32]. Altered scapular kinematics could be linked to pain in the region of the neck [33].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperkyphosis causes excessive scapular protraction and downward rotation. [ 11 , 12 ] Thoracic erector spinae (TES) and rectus abdominis (RA) muscle activity are affected by trunk posture [ 13 ] ; especially, a flexed trunk posture inhibits TES and shortens RA. In addition, previous studies reported that TK is positively associated with forward head posture (FHP).…”
Section: Introductionmentioning
confidence: 99%